Strategi Riau Televisi (Riau TV) Menghadapi Persaingan dengan TV Nasional untuk Tetap Eksis Sebagai TV Lokal - Syafri, Peramasdino; Pannindriya, Sri Tunggul (Eko dan Bisnis: Riau Economic and Business Review, 2019)
Riau Televisi (Riau TV) is the first local television station in the Riau region located in the city of Pekanbaru. As a local television station in Riau, Riau TV clearly has to compete with national television stations, in fighting for viewers in the Riau region. In order to be able to compete with broadcasts from national television, as local television, Riau TV has a special strategy in broadcasting programs, including for marketing targets. The purpose of this research is to find out the strategy carried out by Riau TV, in facing competition with National TV and maintaining its existence as a local TV in Riau. The theory underlying the research is the theory of Media Ecology by Dimmick and Rothenbuhler. In media ecology theory, Dimmick and Rotherbuhler revealed that media needs life-supporting sources, namely types of content, types of audience. and capital. This study uses descriptive qualitative methods and data collection through interviews with Riau TV directors and management, observation and document collection for research purposes. The paradigm used in this study is constructivism. The main focus in this research is to find out what strategies Riau TV has taken to be able to compete with national TV in maintaining its existence. The results of this study concluded, to be able to compete with National TV, Riau TV has a strategy, among others; (1) Strategies for local content TV programs to capture the local audience market, (2) Strategies to expand cooperation networks with local governments, (3) Strategies utilizing internet technology and (4) Strategies to hold off air activities and special moments